TINGKAT KECACINGAN (Enterobius vermicularis) PADA USIA DINIDI KECAMATAN BENJENG KABUPATEN GRESIK - Riski Dwi Prameswari; Emilda Agasvia; Nur Ibadus Sholihah (Journals of Ners Community, 2020)
The worming disease in children is associated with problems of sanitation and poor hygiene such as lack of attention to the use of footwear, eat food without washing hands first. The worming deseasewill not cause instant death so that as the one reason less attention than infectious diseases. Community circumstances Village of Jogodalu District of Benjeng which lies to the west District of Cerme the condition of the area to which access is less, have rural areas that many rice fields, most homes with state of the floor still base on ground. So there are still many people who careless about the environment and health. While the condition of children who received less attention from parents, there are still many children who like to play in the mud and biting the finger so that it is possible many children infectedwith pinworms (Enterobius vermiculari). The purpose of the study to determine the number of patients with pinworms (Enterobius vermiculari) at the age of 3-6 years in the Village of Jogodalu District of Benjeng Gresik. This study is quantitative descriptive uses primary data. Samples were taken directly to the kindergarten Muslimat NU 135 and early childhood (PAUD) Muslimat NU 32 Al Firdaus in the Villageof Jogodalu District of Benjeng Gresik which suspected of being infected with Enterobius vermicularis byinspection method using perianal swabs (Anal swabs). Based on the examination of 30 samples as many 15 samples were infected with Enterobius vermicularis.